((x-8)*(-4))+4x=y

Simple and best practice solution for ((x-8)*(-4))+4x=y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ((x-8)*(-4))+4x=y equation:


Simplifying
((x + -8)(-4)) + 4x = y

Reorder the terms:
((-8 + x)(-4)) + 4x = y

Reorder the terms for easier multiplication:
(-4(-8 + x)) + 4x = y
((-8 * -4 + x * -4)) + 4x = y
((32 + -4x)) + 4x = y
(32 + -4x) + 4x = y

Remove parenthesis around (32 + -4x)
32 + -4x + 4x = y

Combine like terms: -4x + 4x = 0
32 + 0 = y
32 = y

Solving
32 = y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1y' to each side of the equation.
32 + -1y = y + -1y

Combine like terms: y + -1y = 0
32 + -1y = 0

Add '-32' to each side of the equation.
32 + -32 + -1y = 0 + -32

Combine like terms: 32 + -32 = 0
0 + -1y = 0 + -32
-1y = 0 + -32

Combine like terms: 0 + -32 = -32
-1y = -32

Divide each side by '-1'.
y = 32

Simplifying
y = 32

See similar equations:

| ((x-8)-4)+(-4)=y | | 2b^2-7b+5=0 | | (A^3)+(4A^2)-(3A)+6=0 | | 3a+5=41 | | 5x+4x-8=55 | | z+8+4z=18 | | 4+9z=67 | | y+9+7y=49 | | 5y-2+6y=97 | | 7(4-x)=7 | | y-6=1 | | (2+7z)+(8z-6)-(4+9z)= | | z+7=13 | | 3(x-4)-2(2x-5)=-4 | | 3(8y+5)-2(9y)=57 | | 6y+9=51 | | 7y-5+4y=61 | | 2(x-3+3-x)=5 | | 2(x-3+3*4-x)=5 | | 4t^2-22t=-30 | | 2(x-3+3-4-x)=5 | | 5x+12+x=2x-12 | | 28=x^2+3x | | 7x+2=5+3x+9 | | x=3(-62)+8 | | -3+2x-6=3-4x | | -4(3y+8)+11y=30 | | 2x-4+5x=x+2 | | -3x+8(x+2)=17 | | 6x+2x-3+2=-10+9(2x-3)-x | | 6x+22x-3+2=-10+9(2x-3)-x | | 4x+2(4x-4)+4=-11+8(4x-4)-x |

Equations solver categories